Design and optimization of immediate release tablet of salbutamol sulphate by direct compression technique - Saha, Suman (Journal of Applied Pharmaceutical Research, 2018)
This study is about a tablet, which disintegrates or dissolves quickly when placed in the oral cavity. Studies on formulation development of Salbutamol Sulphate Immediate Release Tablet, suitable for manufacturing by direct compression have been carried out. Trial formulations using various excipients were developed and evaluated for various qualities like hardness, friability, disintegration time, content uniformity and dissolution. Study concluded that Immediate Release Tablet of Salbutamol Sulphate can be prepared successfully with added patient benefit and increased consumer satisfaction.